Introduction to econometric theory - Kuan, Chung-Ming (Taipei, 2012)
This chapter summarizes some important results of linear and matrix algebra that are instrumental in analyzing the statistical methods in subsequent chapters. The coverage of these mathematical topics is rather brief but self-contained. Readers may also consult other linear and matrix algebra textbooks for more detailed discussions; see e.g., Anton (1981), Basilevsky (1983), Graybill (1969), and Noble and Daniel (1977).